PARTISIPASI ANGGOTA KELOMPOK WANITA TANI PADA PROGRAM PENANGKARAN BENIH PADI SAWAH UPSUS PAJALE (Studi Kasus di Kelurahan Kawangu Kecamatan Pandawai Kabupaten Sumba Timur) - Saragih, Elsa Christin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Upaya Khusus Padi Jagung dan Kedelai program (Upsus Pajale) is one of the efforts to support self-sufficiency in rice, corn and soybeans in Indonesia. In East Sumba Regency, the implementation of the program is by breeding paddy rice seeds in Kawangu Village, Pandawai District. The purpose of this study was to determine the level of participation and the factors that were significantly related to the participation of women members of farmer groups in the Upsus Pajale program in Kawangu Village, Pandawai District, East Sumba Regency. The sample in this study were all members of the Marangga Pandulang Women’s Farmer Group, totaling 21 people, which were the farmer groups selected in the implementation of the Upsus Pajale rice seed breeding program in East Sumba. The method of data collection is by interview using a questionnaire that has been tested for validity and reliability. Data analysis using Likert Scale and Rank Spearman correlation. The results showed that the level of participation of women farmer groups in the implementation of the Upsus Pajale rice seed breeding program was medium (80,95%) with average score of 101,81, and the processed results of the Spearman Rank correlation data showed a significant relationship between land area, income, capital assistance and the availability of inputs for participation rates. Meanwhile, the motivation and experience factors proved to have no effect on the level of participation of members of the women’s farmer group in the Upsus Pajale program.